Liderazgo directivo en la gestión escolar desde el enfoque político de la escuela - Contreras Paredes, Blanca Margarita (2009)
This investigation presents the analysis of the relationship between the leadership style of a principal and the participation of teachers and students in school management, from a school and leadership political approach. The study identifies the sources of power from the principal of the school; describes how she develops communications with the different school actors; how she implements her decision-making and how she manages conflicts, among other aspects ofmicro-politics. Similarly, the study details how leadership is influential in the participation levels of teachers and students in school management. Finally, the study contributes in identifying management obstacles, in a context that demands a horizontal approach to the relationship principal-teachers-students, suggesting what to do and what not to do by the leadership.